First Full Beta-Strength Measurement With Dtas Across N=126 at Fair Phase-0 - Rodriguez-Garcia D.; Tain J.L.; Morales A.I.; Aggez G.; Agramunt J.; Alaqeel M.; Alayed B.; Albers H.M.; Alcala G.; Algora A.; Alharbi A.; Alhomaidhi S.; et al. (EPJ Web of Conferences, 2023)
An experiment was performed at GSI with the objective of measuring theβ-intensity distribution in the decay of Hg, Au and Pt isotopes around N=126 using the total absorption gamma-ray spectroscopy technique. The aim is to benchmark theoretical models used to make predictions of half-life and neutron emission probabilities of exotic nuclei involved in the rapid neutron capture process, leading to the synthesis of very heavy elements. This paper presents some experimental details and the current status of the analysis.